ANALISIS MASLAHAH TERHADAP WAKAF MUAQQAT (Studi Pasal 1 ayat 1 UU |No. 14/2004 tentang Wakaf) - Makinudin, - (Irtifaq, 2016)
Waqf is one part of alms. In Islamic community assumes that wakaf is muabbad not muaqqat. If wakif has pronounced the pledge of waqf, then the object that is represented out of his possession can not be withdrawn based on Shafi'i school so that if there is another opinion, they reject it, whereas the wakaf is a matter of ijtihad. Article 1 Paragraph 1 of UU Wakaf 41/2004 explains that wakaf is a muabbad and muaqqat, in contrast to the previous regulation, namely Government Regulation No. 28/1977 concerning Ownership of Land Owned and Compilation of Islamic Law by combining several schools of Malikiyyah, H{anafiyyah, Shafi'iyyah, and Malikiyyah by way of talfiq. The implementation of wakaf muaqqat in accordance with ulama Ma>likiyyah which states that the waqf objects can not be separated from the ownership of wakif and H}anafiyyah, who argue that wakaf is like 'a>riyah (loan), which can be withdrawn at any time. Meanwhile, from the side mas} lah} ah, the mueqqat wakaf, which is part of Article 1 paragraph 1 of UU No. 41/2004 is included in mas}lah>ah ha>jiyyah (secondary), which is refining mas}lah}ah d}a>ruriyyah (primary) related to keeping the offspring (muh}a>faz}ah 'ala> nas}l/al-nasab), so avoid the wakif family in poor condition.Keyword : Wakaf muaqqat, UU 1/2004, d}aru>riyyah, h}a>jiyyah.